PEMETAAN DAERAH RAWAN KEKERINGAN DI BALI-NUSA TENGGARA DAN HUBUNGANNYA DENGAN ENSO 2) MENGGUNAKAN APLIKASI DATA PENGINDERAAN JAUH - Nuarsa, I Wayan; Adnyana, I Wayan Sandi; As-syakur, Abd. Rahman (Bumi Lestari Journal of Environment; Vol 15 No 1 (2015))
In this study, the use of SPI (Standardized Precipitation Index) combined with remote sensing data is performed to map vulnerable drought areas in Bali-Nusa Tenggara regions. Analysis also carried out to find the relationship between Vulnerable drought areas in Bali-Nusa Tenggara with El Niño phenomena. Bali-Nusa Tenggara islands are a chain of islands that has a semi-arid climate type and resulted vulnerable to meteorological drought. Therefore, mapping of vulnerable drought areas in the region necessary to be carried out. The spatial pattern of the annual average value of SPI-6 in Bali Nusa Tenggara areas in 1998-2010 indicates the spatial distribution follows the ENSO events. It also indicated in the spatial pattern relationship between ENSO and SPI in Bali-Nusa Tenggara islands. This study indicates that remote sensing data such as TRMM 3B43 has the capability to be used as a data source to analyze the spatial patterns of vulnerable drought areas, particularly in the Bali-Nusa Tenggara Islands. In addition, the TRMM data also possible to be used as a data source to analyze the vulnerable drought areas in other parts of Indonesia.
Keywords: SPI, drought, remote sensing, Bali-Nusa Tenggara, TRMM